Neuronal apoptosis in the neonates born to preeclamptic mothers. (July 2013) - Cosar, Hese; Ozer, Erdener; Topel, Hande; Kahramaner, Zelal; Turkoglu, Ebru; Erdemir, Aydin; Sutcuoglu, Sumer; Bagriyanik, Alper; Ozer, Esra Arun
Abstract Objective: Preeclampsia may result in uteroplacental insufficiency and chronic intrauterine fetal distress. The aim of this study is to address this issue investigating neuronal apoptosis in an experimental model of preeclampsia and to evaluate the neurological outcome of the perinatal asphyxia in the neonates born to preeclamptic mother. Materials and methods: Two out of four pregnant Sprague–Dawley rats (preeclamptic group) were given water containing 1.8% NaCl on gestation day 15 and 22 in order to establish the model of preeclampsia whereas other two (non-preeclamptic group) received normal diet. A model of perinatal asphyxia was established on the postnatal 7th day to one preeclamptic and one non-preeclamptic dam. Overall 23 pups born to overall four dams were decapitated to assess neuronal apoptosis by the TUNEL assay. Results: The number of apoptotic neuronal cells was significantly higher in the preeclampsia groups in comparison with the control group (p = 0.006 and p = 0.006, respectively). It was also significantly higher in the asphyctic/non-preeclamptic group than the count in the control group (p = 0.01). There was also significant difference between both asphyctic groups (p = 0.003). Conclusion: We conclude that preeclampsia causes small babies for the gestational age and cerebral hypoplasia. Both preeclampsia and perinatal asphyxia can cause increased neuronal apoptosis in the neonatal brains. However, the prognosis for neurological outcome is much worse when the perinatal asphyxia occurs in newborns born to preeclamptic mothers.